The Correlation Between Perceived Stress Levels and Academic Self-Efficacy Experienced by UPCD Preclinical Students During the COVID-19 Pandemic/Faith Ashley C. Chua and Mikaela Alessandra I. Millan. - Chua, Faith Ashley C.; Millan, Mikaela Alessandra I.; Paghubasan, Christian Noel E. (2023)
INTRODUCTION: The COVID–19 pandemic has taken a toll on everyone in all
aspects of life: physically, mentally, emotionally, financially, and even
academically. For students, this meant having to participate in a drastic shift to an
online setting for school. Completing school requirements, studying for exams, and
taking online exams in the midst of a global pandemic all pose daunting
challenges. Additionally, students’ academic self–efficacy is constantly called into
question as juggling chores, requirements, and events is a struggle. Furthermore,
added stress may also come from an acquaintance, relative, household member
or the student himself or herself being afflicted with COVID–19. All these serve as
factors that affect students’ prescription of their self–efficacy and academic self–
efficacy in particular.
METHODS: The researchers disseminated an online survey via Google Forms
that included statements from both the Perceived Stress Scale (PSS) & the Online
Learning Self–Efficacy Scale (OLSES), during which students had to rate
themselves on five–point and six–point Likert scales, respectively. After data
collection, descriptive statistics for both the PSS and OLSES were conducted and x
tested for correlational analysis using Spearman’s rank correlation coefficient to
examine the association between the two variables.
RESULTS: Data from 151 eligible respondents showed that 149 (99%) of the
preclinical students were ‘moderately stressed.’ They reported being most
confident in their ability to submit assignments to an online dropbox and in
searching the internet to find the answer to a course–related question but least
confident in their ability to focus on schoolwork when faced with distractions and
use the library’s online resources efficiently. The mean online learning self–efficacy
score for the entire sample was 81.6%, indicating that the overall level of online
self–efficacy of the students was quite high. However, there is a higher number,
80 (53%) out of the 151 respondents, belonging to very low, low, and medium self–
efficacy groups. This implies that students have had trouble adjusting and studying
under the framework of online learning.
CONCLUSION: There is a weak negative correlation between perceived stress
levels and academic self–efficacy of UPCD preclinical students during the COVID–
19 pandemic.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Stress; Dental students--University of the Philippines